The Optimization of Educational Management Through Efficient Financial Management: A Literature Review - Nuraini, Betti; Rimbano, Dheo; Gunadi, Gunadi; Mulyadi, Mulyadi; Judijanto, Loso (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study aims to explore and analyze various strategies for efficient financial management as part of optimizing educational management in schools. Using a literature study method (Library Research) that is qualitative in nature, the research finds that decentralization of educational management provides flexibility in budget allocation according to local needs, but also requires strict supervision to ensure efficiency and transparency. Transparency in financial management is key to preventing budget misuse and enhancing public participation, which in turn contributes to the success of education. Additionally, the implementation of technology, such as e-budgeting applications and web-based reporting systems, can improve efficiency, transparency, and accountability in managing educational budgets. This technology also facilitates monitoring and decision-making processes that are faster and data-driven, ensuring more accurate fund allocation and supporting optimal improvements in education quality.